State Constitutions of the United States - Maddex, Robert L., 1942- (Congressional Quarterly, 2006)
Collects, explains, and offers comparison of each of the fifty state constitutions. Its in-depth explorations reveal individual state priorities, the significance of state constitutions and their impact on issues that affect the day-to-day lives of citizens.